2011
DOI: 10.2139/ssrn.1884499
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of Data Breach Litigation

Abstract: Legal privacy scholarship has typically emphasized the various ways in which plaintiffs fail when bringing legal actions against entities when their personal information is lost or stolen. However, this scholarship is based on a limited set of published judicial opinions about large-scale data breaches. Little is actually known about the characteristics and disposition of a representative set of data breach lawsuits. Using a unique sample of manually-collected data from PACER, we analyze the court dockets of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Additionally, banks with breaches experience a significant decline in deposits, and non-banks experience significant declines in sales in the long run. Romanosky et al (2014) empirically investigate the impact of data breaches on litigation risk and the outcomes of data breach litigation. The authors show that federal lawsuits due to data breaches result in a high settlement rate of about 50%.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, banks with breaches experience a significant decline in deposits, and non-banks experience significant declines in sales in the long run. Romanosky et al (2014) empirically investigate the impact of data breaches on litigation risk and the outcomes of data breach litigation. The authors show that federal lawsuits due to data breaches result in a high settlement rate of about 50%.…”
Section: Related Literaturementioning
confidence: 99%
“…See https://www.privacyrights.org/. PRC is the most cited source of information relating to data breaches (e.g.,Kamiya et al, 2020;Romanosky et al, 2014).…”
mentioning
confidence: 99%
“…Our method can be combined with any approach for the quantification of impact. Several studies on the quantification of impact exist, including impact from direct losses, (84,85) technical impacts, (60) financial impacts, (86) and reputational and operational impacts. (87)…”
Section: 70mentioning
confidence: 99%
“…Whereas several studies on the quantification of impact exist, (60,(84)(85)(86)(87) current risk assessment methodologies lack a well-specified method for the measurement of attack likelihood. (23) As discussed in Section 2, in this work we specifically refer to untargeted attacks.…”
Section: A Quantitative Model For Likelihood Of Cyberattacksmentioning
confidence: 99%
“…However, there are also underlying costs associated with each software vulnerability, as mentioned above, and those costs maybe invisible [10]. For example, Romanosky et al [11] studied software-related data breaches in the United States and found that 4% of them resulted in litigation in federal courts, out of which 50% (2% of the original studied cases) were won. Considering no impact of vulnerabilities on vendors, as shown by prior work, the vendors do not seem to face any immediate effect on themselves, unlike the end users.…”
Section: Introductionmentioning
confidence: 99%